2000
DOI: 10.1074/jbc.m004729200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Heme Oxygenase-1 Gene Activation by Cadmium in MCF-7 Mammary Epithelial Cells

Abstract: The mouse heme oxygenase-1 (HO-1) gene, ho-1, contains two inducible enhancers, E1 and E2. Of several cell lines tested, induction of an E1/luciferase fusion construct, pE1-luc, by CdCl(2) is most pronounced in MCF-7 cells. In these cells, E1, but not E2, is necessary and sufficient for ho-1 gene activation. Exposure of MCF-7 cells to 10 micrometer CdCl(2) stimulates phosphorylation of ERK, JNK, and p38 mitogen-activated protein kinases, implicating one or more of these signaling pathways in ho-1 gene inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
250
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 392 publications
(262 citation statements)
references
References 39 publications
9
250
2
1
Order By: Relevance
“…Many studies have reported that HO-1 expression is mainly regulated by Nrf2-dependent ARE activation in several cell types. [44][45][46] Studies of the ectopic expression of Nrf2 and siRNA constructs of Nrf2 and HO-1 further confirmed that the protective effect of flunarizine is indeed through Nrf2/HO-1 in cisplatin-treated cells. Our results also suggest that the AREdriven upregulation of HO-1 gene expression after treatment with flunarizine was mediated by nuclear translocation of Nrf2, not by de novo synthesis of Nrf2 in HEI-OC1.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Many studies have reported that HO-1 expression is mainly regulated by Nrf2-dependent ARE activation in several cell types. [44][45][46] Studies of the ectopic expression of Nrf2 and siRNA constructs of Nrf2 and HO-1 further confirmed that the protective effect of flunarizine is indeed through Nrf2/HO-1 in cisplatin-treated cells. Our results also suggest that the AREdriven upregulation of HO-1 gene expression after treatment with flunarizine was mediated by nuclear translocation of Nrf2, not by de novo synthesis of Nrf2 in HEI-OC1.…”
Section: Discussionmentioning
confidence: 79%
“…Samples were then prepared and analyzed for viability or RT-PCR. promoter (MP) sequence 44 into luciferase reporter plasmid pGL3-Basic. E2 and MP were generated by PCR of mouse cDNA with oligonucleotide pairs E2 SacI: 5 0 -AGC TGA GCT CCT TAA GCA ATC CAT TAG GAA TCC G-3 0 and E2 ApaI: 5 0 -AGC TGG GCC CCC GCT CTC TTG CCA GAC TC-3 0 and MP Apa1: 5 0 -TTA CAG GCA GGG CCC GCC T-3 0 and MP Xho1: 5 0 -TAT GCT CGA GAC GGC TCT GC-3 0 , respectively.…”
Section: Transfection Of Nrf2 Ho-1 and Sirnas Constructs Into Hei-ocmentioning
confidence: 99%
“…Nrf2 activation and its binding to ARE sites in the promoter region are critical in HO-1 expression in human hepatoma HepG2, MCF-7 mammary epithelial, and microglial cells (Alam et al, 2000;Min et al, 2006;Yu et al, 2000). Adenosine also activated Nrf2, as evident from its translocation to the nuclei and increase in Nrf2-ARE binding, which appears important in HO-1 expression in microglia (Figs.…”
Section: Discussionmentioning
confidence: 92%
“…15,75 Phosphatidylinositol 3-kinaseemediated phosphorylation of Nrf2 and its dissociation, nuclear translocation, and subsequent induction of antioxidants have been shown in human neuroblastoma cells. 76 In addition to the involvement of PKC and phosphatidylinositol 3-kinase in the activation of Nrf2, accumulating evidence suggests a role for mitogenactivated protein kinases 19,77,78 ; however, some reports suggest negative regulation of Nrf2 by these protein kinase pathways. 79 For example, extracellular signal regulated kinase 1/2 signaling cascades have been shown to increase the activation/stabilization of Nrf2, leading to induction of cytoprotective genes.…”
Section: Keap1-independent Mechanismsmentioning
confidence: 99%
“…77 Activation of p38 mitogen-activated protein kinase and Janus kinase has also been implicated in the activation and nuclear translocation of Nrf2. 19,78 In contrast, phosphorylation of tyrosine residues (Tyr-568) on Nrf2 by glycogen synthetase kinase 3b activated Fyn has been shown to promote nuclear export and degradation of Nrf2. 79 Acetylation and deacetylation of Nrf2 promote nuclearcytoplasmic shuttling and regulation of its transcriptional activity.…”
Section: Keap1-independent Mechanismsmentioning
confidence: 99%